Hey there!
Here's the answer.
r+9r-5+3r=4 --> Write the problem.
r+9r+3r-5=4 --> Group the r terms together and the constant terms together.
13r-5=4 --> Simplify the above equation.
13r=9 --> Add 5 to both sides of the equation.
r=9/13 Divide 13 on both sides of the equation.
So the answer is r=9/13.
Hope it helps!
2007-07-18 15:47:44
·
answer #1
·
answered by ? 6
·
0⤊
0⤋
r + 9r - 5 + 3r = 4
r + 9r + 3r -5 = 4
r (1 + 9 + 3) - 5 = 4
13r - 5 = 4
13r - 5 + 5 = 4 + 5
13r = 9
13r/13 = 9/13
r = 9/13
(9/13 = 0.692 307 692 3)
2007-07-18 13:07:59
·
answer #2
·
answered by GPC 3
·
0⤊
0⤋
r + 9r - 5 + 3r = 4
13r = 4 + 5
13r = 9
r = 9/13
Proof:
9/13 + 9(9/13) - 5 + 3(9/13) = 4
9/13 + 81/13 - 5 + 27/13 = 4
117/13 - 5 = 4
9 - 5 = 4
Answer: r = 9/13
2007-07-22 02:08:52
·
answer #3
·
answered by Jun Agruda 7
·
2⤊
0⤋
13 r = 9
r = 9 / 13
2007-07-21 12:05:53
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
13r-5=4
13r-5+5=4+5
13r=9
r=9/13
2007-07-18 13:22:03
·
answer #5
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
r+9r-5+3r=4
OR 13R=9
OR R=9/13
2007-07-18 22:16:54
·
answer #6
·
answered by Sumita T 3
·
0⤊
0⤋
10r -5 + 3r = 4
13r - 5 = 4
13r = 9
r = 9/13
r ~= 0.692
2007-07-18 12:52:36
·
answer #7
·
answered by dr_no4458 4
·
0⤊
0⤋
r = 9/13ths
2007-07-18 12:56:08
·
answer #8
·
answered by whiner_cooler 4
·
0⤊
0⤋
0.692
2007-07-18 12:54:50
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋